Review of the National Police Chief's Policy Regarding Decree Number Kep/613/III/2021 Maintaining Public Security and Order in Certain Areas - Rifki Ersanda; Ixora Lundia Suwaryono (UIN Sunan Gunung Djati, 2023)
After the policy of the Chief of Police issued his Decree Number: 613/III/2021 dated March 23, 2021 so that the authority of the Sector Police is reduced to only carrying out investigative activities including receiving reports, requesting information, visiting crime scene, collecting evidence but also to delegate the case to the Resort Police if the crime is continued into the investigations stage, if the crime is continued to the investigation stage it must be delegated to a higher unit, namely the Resort Police. This research is based on the theory of legal certainty and hierarchy. The legal status of the Decree of the Chief of Police Number Kep/613/11/2021 concerning Appointment of Sector Police Only to Maintain Public Security and Order in Certain Areas (Not Conducting Investigations) is that the Decree of the Chief of Police is categorized as a beleidsregel (policy regulation). The Polsek focuses on aspects of Kamtibmas, being in the midst of society, prioritizing the main tasks of protecting, nurturing and serving the community by carrying out pre-emptive and preventive activities rather than repressive and the effectiveness of investigations is handed over to the upper unit level, namely the Polres. Then the decision of the Head of the National Police to remove the investigative authority at the Polsek in the study of criminal law policies is quite rational within the framework of non-penal efforts to solely enforce the law for the realization of security and public order. The impact of the issuance of the decision to stop investigations and investigations at the Polsek, the stipulation of the Decree of the head of the National Police of the Republic of Indonesia Number: Kep/613/III/2021 made it difficult for the community. People who live far from the Polres use paid transportation and are not ready for transportation. The police are unable to handle cases. The community feels that the authority of the police is burdened in enforcing the law because it is more expensive. Abolishing investigative powers is also beneficial for the police, because basically law enforcers must be closely monitored, while so far supervision at the police level has been very weak. Eliminating the right to investigate can minimize the potential for abuse of authority. Another advantage, the abolition of investigative authority can also make the Police closer and become friends of the community. Because on the one hand the police can focus more on working with the community to maintain order, and on the other hand eliminate negative perceptions such as repression that generally arise when they handle cases.